Comparative Study On Diesel Engine Performance Operatingwith Biodiesel And Diesel Fuel - R., Mamat (2010)

(untitled)
The main objective of this research is to compare the performance of direct injection diesel engine operating with biodiesel and diesel fuel. Based on GT-Power simulation, the effects of using biodiesel fuel had been analyzed. The specifications of engine follow the diesel engine Mitsubishi 4D68, four cylinders, four stroke, and 50-kW power capacity. These comparison studies were conducted on both engine power and characteristics of each fuel. The simulation results showed that torque and power outputs for biodiesel fuel were generally lower than those for diesel fuel.